Supervisors’ self-assessment of feedback skills: a psychometric validation study of the English version of the SwissSETQ questionnaire for supervisors - Fabienne Schwitz; Joy Backhaus; Monika Brodmann Maeder; Eva K. Hennel (Swiss Medical Weekly)
STUDY AIMS: We created an instrument to assess the supervisors’ perspective on their feedback behaviour to residents and investigated its validity. Our instrument is based on the SETQsmart, a Dutch instrument for assessing the quality of supervision in clinical training and the SwissSETQ, its German adaptation for residents. Our instrument is in English to ensure relevance across all Swiss language regions. The study specifically sought: to replicate the factor structure of the original trainee questionnaire for supervisors; to verify the alignment of SwissSETQ and SETQsmart domains with the factor structure; and to evaluate the psychometric properties of the English version.